An improved CPF for static stability analysis of distribution systems with high DG penetration. (March 2017) - Dou, Xiaobo; Zhang, Shizhan; Chang, Limin; Wu, Zaijun; Gu, Wei; Hu, Minqiang; Yuan, Xiaodong
Highlights: An improved continuation power flow method for distribution systems with a high penetration of distributed generation is proposed. The comprehensive static characteristics bus models are established to indicate the components in distribution systems. The distributed slack bus model based on incremental loss factors is used to allocate unbalanced power. The net load growth pattern is proposed to evaluate the effect of the intermittency and fluctuation of renewables on the static stability. Abstract: This paper proposes an improved continuation power flow (CPF) method for the modelling and stability analysis of distribution systems with a high penetration of distributed generation (DG). This method aims at solving the flaws of conventional CPF in the description of DGs, the allocation of unbalanced power and the consideration of renewables. To indicate the power variations of DGs with respect to terminal voltage and system frequency precisely, the comprehensive static characteristics bus models are introduced into the calculation of the equilibrium point. Then, in the case of multiple generations, the distributed slack bus model based on incremental loss factors (ILFs) is used to allocate unbalanced power, making the results of CPF independent of slack bus selection. In addition, the load growth pattern involving the output characteristics of renewables is reinterpreted as the net load growth pattern to reflect the intermittency and fluctuation of renewables on the static stability of distribution systems. A detailed solution process of improved CPF is then elaborated. Case studies are presented on the IEEE 33-bus distribution system to illustrate the validity of the improved CPF method, and more simulations on the PG&E 69-bus distribution system are performed to assess the effect of DGs on the static stability of distribution systems.